2020
DOI: 10.3390/jcm9030833
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Complexity in Anorexia Nervosa: A Fractal Dimension Analysis

Abstract: Fractal Dimension (FD) has shown to be a promising means to describe the morphology of cortical structures across different neurologic and psychiatric conditions, displaying a good sensitivity in capturing atrophy processes. In this study, we aimed at exploring the morphology of cortical areas by means of FD in 58 female patients with Anorexia Nervosa (AN) (38 currently underweight and 20 fully recovered) and 38 healthy controls (HC). All participants underwent high-resolution MRI. Surface extraction was compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 42 publications
0
33
0
Order By: Relevance
“…FD measurement is a sensitive method for describing the atrophy of cortical structures in neurologic and psychiatric conditions [ 44 ]. Studies using voxel-based morphometry (VBM) have found a globally reduced GM volume, but inconsistent results have emerged in identifying regional changes in neurodegenerative disease [ 29 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…FD measurement is a sensitive method for describing the atrophy of cortical structures in neurologic and psychiatric conditions [ 44 ]. Studies using voxel-based morphometry (VBM) have found a globally reduced GM volume, but inconsistent results have emerged in identifying regional changes in neurodegenerative disease [ 29 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients of the Padova site (aka Site 1) were consecutively recruited from the Padova Hospital Eating Disorders Unit. The sample included was the same as in previous studies (Favaro et al, 2013; Collantoni et al, 2020). Patients were recruited if meeting full criteria for AN, as assessed with the Structured Clinical Interview for DSM‐5 (American Psychiatric Association, 2013) by experienced consultants.…”
Section: Methodsmentioning
confidence: 99%
“…FD has been extensively applied to investigate morphological changes in the cerebral cortex caused by neurological diseases [ 16 , 17 , 18 ]. The procedure of FD computation is as follows.…”
Section: Methodsmentioning
confidence: 99%
“…FD is complementary to volumetric measures and may assist in identifying disease state or disease progression [ 16 ]. Furthermore, FD has been shown to be a promising means for describing the morphology of cortical structures across different neurologic and psychiatric conditions, with good sensitivity in capturing atrophy processes [ 17 ].…”
Section: Introductionmentioning
confidence: 99%